Application of a IGCT for Pulsed Power - YAN Ji; LEI Yun; REN Yadong; PAN Xuejun; ZENG Wenbin; YU Wei; XIONG Siyu (Kongzhi Yu Xinxi Jishu)
It introduced a power semiconductor (IGCT) applied in pulsed power, including the device and the structure. IGCT is suitable for pulsed power applications owing to high current and high di/dt capability. Pulse discharge test was completed and then applications of the IGCT in series were discussed.